Legal Protection against Revenge Porn: A Comparative Criminal Law Analysis of Indonesia and Laos: Perlindungan Hukum terhadap Pornografi Balas Dendam: Analisis Perbandingan Hukum Pidana antara Indonesia dan Laos - Nikmatul Keumala Nofa Yuwono; Wahyudi Ikhsan (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Non-consensual dissemination of intimate images constitutes technology-facilitated gender-based violence that causes persistent psychological, social, economic, and privacy-related harm. Specific Background: Southeast Asian legal systems address this offense through divergent criminal doctrines shaped by different political, cultural, and institutional traditions. Knowledge Gap: Comparative scholarship has rarely examined the statutory criminalization and recovery mechanisms applied in Indonesia and the Lao People’s Democratic Republic. Aims: This study compares both jurisdictions’ criminal policies and evaluates their capacity to provide substantive justice for survivors. Results: Normative legal research was conducted through statutory, conceptual, and comparative criminal law approaches. Indonesia expressly recognizes electronic-based sexual violence under Law No. 12 of 2022, placing absence of consent, bodily autonomy, digital privacy, and gender-based power relations at the center of criminal liability. Its framework provides restitution, a victim assistance fund, and content-removal mechanisms. The Lao legal system contains no specific offense for non-consensual intimate image distribution and instead relies on pornography, indecent behavior, cybercrime, and cultural morality provisions. Reliance on Village Mediation Committees prioritizes communal harmony and informal compromise, creating substantial risks of secondary victimization and perpetrator impunity. Novelty: The study connects differences in criminalization doctrine with the practical architecture of survivor recovery in two contrasting Southeast Asian legal systems. Implications: Lao legislation requires a consent-based autonomous offense, formal reparative mechanisms, and removal of mandatory community mediation, while Indonesian institutions require gender-sensitive enforcement and consistent execution of restitution and digital erasure rights. Highlights: The first jurisdiction expressly criminalizes electronic sexual abuse through the absence-of-consent principle. The second jurisdiction relies on morality, obscenity, cyber-security, and communal dispute mechanisms. Restitution, financial assistance, and digital content removal provide a more comprehensive recovery structure. Keywords: Revenge Porn, Comparative Criminal Law, UU TPKS, Lao Penal Code, Non-Consensual Intimate Images